1984
DOI: 10.1016/0010-938x(84)90025-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative pitting corrosion study of mild steel in different alkaline solutions containing salts with sulphur-containing anions

Abstract: The localized corrosion of mild steel in alkaline solutions containing a salt with a sulphurcontaining anion (sodium sulphate, sodium sulphite, sodium thiosulphate, potassium thiocyanate and sodium sulphide) is studied by using potentiostatic and potentiodynamic techniques complemented with scanning electron microscopy. Alkaline solutions containing one of those salts produce pitting of mild steel at potential values more positive than those of the active-passive transition of iron in base. In the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Similar studies were reported [5][6][7][8][9][10][11][12][13][14][15][16][17] for mid steel corrosion in chloride contaminated alkaline medium by electrochemical studies and the inhibitors repassivated the steel surface and reduce the pitting corrosion. The present work is also focused on the evaluation of corrosion resistance performance novel inhibitor for mild steel corrosion in chloride contaminated alkaline solution.…”
Section: Introductionsupporting
confidence: 81%
“…Similar studies were reported [5][6][7][8][9][10][11][12][13][14][15][16][17] for mid steel corrosion in chloride contaminated alkaline medium by electrochemical studies and the inhibitors repassivated the steel surface and reduce the pitting corrosion. The present work is also focused on the evaluation of corrosion resistance performance novel inhibitor for mild steel corrosion in chloride contaminated alkaline solution.…”
Section: Introductionsupporting
confidence: 81%
“…S-metal interactions are extremely important because S is a poison for many heterogeneous reactions involving different metallic catalysts [27,[48][49][50][51] in some technological processes of great economical interest. In fact, S layers can be formed on metal surfaces as an undesired result of the adsorption and reaction of different compounds, such as SO 2 , disulfides, alkanethiols, thiosulfates, thiocyanates, and sulfides [52,53]. Also, recently it has been found that oxide-supported metallic nanoparticles have excellent catalytic properties [54,55], an issue nowadays of great concern for future technological developments.…”
Section: Thiol and Sam Applicationsmentioning
confidence: 99%
“…The corrosion process is studied using electrochemical techniques complemented with scanning electron microscopy. Pit initiation of nickel in the various systems investigated can be interpreted through the same complex mechanism already applied to the pitting corrosion of iron (12).…”
mentioning
confidence: 89%